Evaluating android smartphone’s bluetooth received signal strength indicator measurements for social distancing - Majid Faleh Alanezi; Muhammad Tajammal Chughtai (Institute of Advanced Engineering and Science, 2022)
This paper presents a digital solution to reduce transmission of coronavirus disease 2019 (COVID-19) by maintaining social distance between the general public. The object is achieved by using bluetooth, which is already handy for almost everyone in the general public and comes as a standard feature in smartphones. The present technique uses an indirect method to calculate the range between the two objects. 5,300 samples were collected by adjusting the receiver at a range of angles to calculate the intensity of the bluetooth signal. The observations are presented in the form of plotted graphs between the number of samples and the average received signal strength indicator (RSSI) value at a particular angle of rotation.